Easy Shell Repair - Forrester, Harriet; Satta, John (Wildlife Rehabilitation Bulletin, 2005)
Repair of certain chelonian shell fractures can be performed without screws, wires, drilling, or patches. The authors have used this procedure successfully on a number of species, including snapping turtles (Chelydra serpentina), painted turtles (Chrysemys picta), sliders (Trachemys spp.), and diamondback terrapins (Malaclemys terrapin). The process is quick and minimally stressful for the turtle.